1995
DOI: 10.1095/biolreprod52.4.721
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Muscarinic Agonist Carbachol on Intracellular Ca2+ in Chicken Granulosa Cells: I. Dependence on Follicular Maturation1

Abstract: The present study addressed the influence of follicular development on carbamylcholine chloride (Cch)-induced Ca2+ transients and inositol 1,4,5-trisphosphate (IP3) production in granulosa cells isolated from the first (F1), third (F3), and fifth and sixth (F5,6) largest follicles. Intracellular free calcium, [Ca2+]i, was measured in fura-2-loaded cells about 20-36 h after their isolation. The percentage of cells responding to a maximal stimulatory concentration of Cch (0.2 mM) was higher in the F1 (89%) granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Consequently, we attribute the inability of this portion of the granulosa cell population to mobilize intracellular Ca 2+ to their failure to access and/or fill Ca 2+ stores. We propose that TNFa facilitates 1) the filling of these stores by either activation of Ca 2+ -ATPases on Ca 2 + stores with a concomitant influx of extracellular Ca 2 + or via an influx of extracellular Ca 2+ directly into these Ca 2 + stores as suggested by the model of capacitive Ca 2 + entry [25] or 2) Cch-induced IP 3 production, as we have previously demonstrated that fast Ca 2+ transients in F1 cells are mediated by IP 3 [23]. Determining which (if any) of the mechanisms proposed above accurately describe the mechanisms behind the TNFa-Cch interaction will require further experimentation.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Consequently, we attribute the inability of this portion of the granulosa cell population to mobilize intracellular Ca 2+ to their failure to access and/or fill Ca 2+ stores. We propose that TNFa facilitates 1) the filling of these stores by either activation of Ca 2+ -ATPases on Ca 2 + stores with a concomitant influx of extracellular Ca 2 + or via an influx of extracellular Ca 2+ directly into these Ca 2 + stores as suggested by the model of capacitive Ca 2 + entry [25] or 2) Cch-induced IP 3 production, as we have previously demonstrated that fast Ca 2+ transients in F1 cells are mediated by IP 3 [23]. Determining which (if any) of the mechanisms proposed above accurately describe the mechanisms behind the TNFa-Cch interaction will require further experimentation.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, it has been demonstrated that Ach increases ovarian oxytocin and progesterone secretion in vivo in sheep [40] and bovine granulosa cell oxytocin and progesterone production in vitro [41]. Previous studies from our laboratory have demonstrated that muscarinic input has at least two mechanisms of action in hen granulosa cells: increasing [Ca 2+ ]i [22,23] and intracellular pH [42]. Moreover, data from the present study has demonstrated that the nature and magnitude of the Cchinduced Ca 2 + transient are modified by pretreatment with TNFa, and that this TNFa effect increases with follicular development.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, the ability of PGE 2 to override the suppression of [ 3 H]thymidine incorporation into DNA by PLA 2 inhibitor was greater in cells at the earlier than at the later stage of follicular maturation. It would be of interest to determine whether these follicular stage-dependent differences are the result of programmed changes in granulosa cell PG receptor abundance and/or production or activation of factor X, as has been previously suggested [33,34].…”
Section: Discussionmentioning
confidence: 99%